The Idea of Cross-Religious Dialogue in the Time of the Covid-19 Pandemic - Ahmad Zainuri; M. Khusna Amal (LPPM IAIN Kudus, 2023)
Interfaith dialogue is one of the keys to building harmony among religious believers. Religious intolerance and religious discrimination have spread throughout this country during the Covid-19 pandemic. Freedom of religion is still an issue that reaps violence in the end. Negative religious fanatics are not recommended in responding to diversity and existing realities. It is feared that it will have an impact on conflicts with religious nuances that have no completeness. The method used in this article is based on the theoretical concept of “interfaith dialogue”. So the result is that the idea of interfaith dialogue during the Covid-19 pandemic has become one of the important formulas in religious moderation. For example, interfaith dialogue in education, social, community and social media. It can be concluded that interfaith dialogue in these times of the Covid-19 pandemic is very necessary. Good for moral education, building religious and social diversity, and peaceful literacy with the aim of countering extremist narratives, discrimination, and intolerance on social media and in social life.